O Programa Ler e Escrever e o ensino e aprendizagem da leitura e escrita: estudo de caso - Balbino, Keila Tatiane da Silva (2016)
School activities are commonly targeted by educational projects aimed at learning how to read and write. The fact that the Programa Ler e Escrever (PLE) is one of the main drivers of school education program adopted by the State of São Paulo's educational system has led us to question how the actors involved in this process - teacher and students - respond to this proposal. The research objectives were to monitor and analyze the implementation of PLE with regard to teaching and learning to reading and writing. The specific objectives were to analyze the proposals of the Teacher's Guide, follow how the teacher applies the teaching materials, analyze the activities of students and match the findings, to achieve the main goal. For this work we chose the methodology of case instrumental study of descriptive and qualitative character. The subjects were the teacher and the students of the 2nd year of primary education in a state school in São Paulo. The results suggest that the activities proposed by the PLE, the way led by the teacher, were little challenging for students who already knew how to read and write. In relation to those who were illiterate, the fact that the teacher fail to follow the guidelines of the Teacher's Guide appears to have interfered negatively on learning. From the analysis of the production of the students that did not achieve the goals set in the Teacher's Guide, we observe a further indication that the autonomy of the teacher in relation to the guide, may have committed their learning